How Can Product Delivery Efficiency Be Improved? A Comparative Study Between the Shortest Path Method and Vehicle Routing Problem with Pool Clustering Implementation in Kukami Delivery Subang - Muhammad Ridlan Akbar; Didit Damur Rochman (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Due to the volume of orders and network complexity, KUKAMI Delivery faces high operational costs and suboptimal routing using the Shortest Path Method. This method often results in inefficient routes in terms of distance because the starting points could be more optimal. Therefore, a more practical approach is needed to improve route efficiency. This study compares two route optimization methods: the Shortest Path Method and the Vehicle Routing Problem (VRP) with the Saving Matrix approach and Pool Clustering. The latter technique groups partners or suppliers within specific areas, facilitating more efficient rider assignments. The results of this study are significant for KUKAMI Delivery. They show that the Shortest Path Method can improve distance and operational costs by 8.8% for both inter-cluster and cross-cluster routes. However, applying the VRP with the Saving Matrix Method and Pool Clustering can further enhance distance and operational efficiency by 3.36% compared to the Shortest Path Method. These findings provide valuable insights for enhancing KUKAMI Delivery’s operations to better meet the growing demand in the local delivery industry.